Shoulder muscle recruitment patterns during a kayak stroke performed on a paddling ergometer - Trevithick, B. A.; Ginn, K. A.; Halaki, M.; Balnave, R. (Journal of Electromyography and Kinesiology, 2007)
Precise muscle co-ordination is required to maintain normal shoulder function and alterations in synchrony between shoulder muscles can result in loss of full range of movement and pain. Although shoulder pain in kayakers is high with 53% of elite international paddlers reporting shoulder injuries, little information is available regarding the pattern of shoulder muscle recruitment during paddling. The aim of this study was to investigate the normal recruitment pattern of shoulder muscles during the kayak stroke. Nine recreational paddlers without shoulder pain were examined. EMG data from eight shoulder muscles of the dominant arm were collected simultaneously with video data during simulated paddling on an ergometer. EMG data was normalized to time and peak amplitude. Intersubject consistency was evaluated using Pearson correlation analysis. The results of this study indicated a fair to high correlation in at least one phase of the kayak stroke in five of the muscles examined: upper trapezius, supraspinatus, latissimus dorsi, serratus anterior and rhomboid major. This normative data will enable comparisons with the shoulder muscle recruitment patterns in kayakers with shoulder pain in order to determine the role of altered motor control in the painful kayaking shoulder.